'Business as usual': The Treaty of Lisbon and transnational party manifestos; Business as usual: el Tratado de Lisboa y los programas de los europartidos - Cristina Ares; Andrea Volkens (Política y Sociedad, 2021)
The Treaty of Lisbon was a milestone in the enduring process of empowerment of the European Parliament and its connections to the European Commission. This latest reform of the Treaties, in force since December 2009, placed the only supranational institution whose members are directly elected by all citizens of the EU (since 1979) on an equal footing with the Council as a co-legislator in around thirty additional policy areas. The Treaty of Lisbon also strengthened the European Parliament in terms of the annual and multiannual budgetary decisions, and it granted it the right to elect the President of the European Commission according to the results of the European elections. This article examines various possible effects of this major boost of the European Parliament, along with links to the European Commission in the manifestos issued by five European parties: the Alliance of Liberals and Democrats for Europe (ALDE), European Free Alliance (EFA), European Green Party (European Greens or EGP), European People's Party (EPP), and Party of European Socialists (PES). It studies variations from 2004 onwards in the scope of the programmatic proposals regarding EU domains of power, the footprint in the manifestos of the transnational party organisations themselves, and eventually also of their candidates for the presidency of the European Commission. To do so, the twenty manifestos issued by the abovementioned parties for the 2004, 2009, 2014 and 2019 European elections were content analysed. The results point to the lasting distance between these transnational parties and the European elections, despite the reinforcement of the role of the European Parliament over time. – – El Tratado de Lisboa supuso un auténtico hito en el proceso de fortalecimiento del Parlamento Europeo y de sus vínculos con la Comisión Europea. Esta última reforma de los Tratados, en vigor desde diciembre 2009, situó la única institución supranacional elegida directamente por todos los ciudadanos de la UE —desde 1979—, en pie de igualdad con el Consejo en tanto que colegisladora en alrededor de treinta nuevas áreas de políticas. El Tratado de Lisboa robusteció asimismo el Parlamento Europeo en las decisiones presupuestarias anuales y plurianuales, y le otorgó el derecho a elegir al presidente de la Comisión de acuerdo con los resultados de las elecciones europeas. El artículo examina algunos posibles efectos de este refuerzo del Parlamento Europeo y de su relación con la Comisión Europea en los programas de cinco partidos políticos a escala europea, que son la Alianza de los Liberales y Demócratas por Europa (ALDE), Alianza Libre Europea (ALE), Partido Verde Europeo (Verdes Europeos o PVE), Partido Popular Europeo (PPE) y Partido Socialista Europeo (PSE). Se estudió la variación a partir de 2004 en la extensión de las propuestas programáticas sobre los asuntos que son competencia de la UE, la eventual huella en sus programas de las propias organizaciones de partido a escala europea, así como de sus candidatos a presidir la Comisión Europea. Para ello, se llevó a cabo un análisis de contenido de los veinte programas presentados para las elecciones de 2004, 2009, 2014 y 2019 por parte de los partidos mencionados. Los resultados apuntan a la persistente distancia entre estos partidos transnacionales y las elecciones europeas, pese al impulso del papel del Parlamento Europeo a lo largo del tiempo.
Keywords: 300; European Parliament; European parties; ALDE; EFA; EGP; EPP; PES; Parlamento Europeo; partidos políticos a escala europea; ALE; PVE; PPE; PSE